2015
DOI: 10.1002/pmic.201500029
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of human plasma identifies apolipoprotein E as being associated with smoking and a marker for squamous metaplasia of the lung

Abstract: Biomarkers to identify subjects at high-risk for developing lung cancer will revolutionize the disease outlook. Most biomarker studies have focused on patients already diagnosed with lung cancer and in most cases the disease is often advanced and incurable. The objective of this study was to use proteomics to identify a plasma biomarker for early detection of lung lesions that may subsequently be the harbinger for cancer. Plasma samples were obtained from subjects without lung cancer grouped as never, current,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Similarly, pleural fluid apoE levels were higher in malignant as compared with benign pleural effusions, especially those associated with adenocarcinomas (52). Collectively, these studies suggest a role for apoE in promoting lung cancer, perhaps by enhancing cholesterol transport into tumor cells (50). Consistent with this concept, LDLR expression is up-regulated in the A549 human lung adenocarcinoma cell line and increases when cholesterol is depleted (53).…”
Section: Apoe and Lung Cancersupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, pleural fluid apoE levels were higher in malignant as compared with benign pleural effusions, especially those associated with adenocarcinomas (52). Collectively, these studies suggest a role for apoE in promoting lung cancer, perhaps by enhancing cholesterol transport into tumor cells (50). Consistent with this concept, LDLR expression is up-regulated in the A549 human lung adenocarcinoma cell line and increases when cholesterol is depleted (53).…”
Section: Apoe and Lung Cancersupporting
confidence: 73%
“…Proteomic profiling of human plasma has identified elevated levels of apoE in current smokers as compared with nonsmokers (50). Similarly, a significant positive correlation was observed between plasma apoE levels and premalignant squamous metaplasia.…”
Section: Apoe and Lung Cancermentioning
confidence: 76%
“…For example, alpha‐1‐acid glycoprotein 1 (ORM1) has been detected in non‐small cell lung cancer and gastric adenocarcinoma, and apolipoprotein A‐IV (APOA4) in ovarian and pancreatic cancers . Likewise, many studies have reported elevated inflammatory markers, such as C reactive protein (CRP) and/or Serum amyloid A‐1 protein (SAA1) . For example, in plasma of patients with lung and liver cancer, and elsewhere in relation to circulation and cardiovascular risk, including atherosclerosis and aortic aneurysms.…”
Section: Methodsmentioning
confidence: 99%
“…It may be possible to use blood proteomics to stratify risk of developing lung cancer. One study applied proteomics to plasma from never, current or former smokers and reported a significant association with plasma apolipoprotein E (APOE) levels and the development of squamous metaplasia in the lungs, supporting the potential to develop proteomic plasma biomarkers capable of predicting pre‐malignant and early forms of lung cancer . However, lung tissue samples from cancer patients have received more extensive analysis.…”
Section: Proteomic Applications In Respiratory Diseasementioning
confidence: 99%